Cordyceps militaris and Armillaria mellea formula alleviates depressive behaviors via microglia regulation in an unpredictable chronic mild stress animal model - Yu-En Lin; Hui-Ping Lin; Kuan-Hung Lu; Yun-Ju Huang; Suraphan Panyod; Wei-Ting Liu; Yun-Sheng Lu; Mei-Hsing Chen; Lee-Yan Sheen (Journal of Traditional and Complementary Medicine)
Background and aim: Cordyceps militaris (CM) and Armillaria mellea (AM) are medicinal mushrooms with potential applications in the treatment of mood disorders, including depression and anxiety. While research suggests that both CM and AM possess anti-inflammatory properties and hold potential for treating depression when administered separately, there is limited knowledge about their efficacy when combined in a formula, as well as the underlying mechanism involving the modulation of microglia. Experimental procedure: Rats received oral administrations of the low-dose formulation, medium-dose formulation, and high-dose formulation over 28 consecutive days as part of the UCMS protocols. The concentrations of serotonin, dopamine, and the corresponding metabolites in the rat prefrontal cortex and hippocampus were assessed. Blood samples were collected to examine corticosterone levels, and the brains were dissected for evaluating activated microglia morphologies and associated pro- and anti-inflammatory signaling pathways. Results and conclusion: The CM-AM formula effectively averted abnormal behaviors triggered by UCMS, such as anhedonia and hypoactivity, and decreased the turnover rate of monoamines in both the prefrontal cortex and hippocampus. The formula mitigated the increase in serum corticosterone levels induced by chronic stress. Furthermore, the formula alleviated stress-induced microglia activation in the hippocampus, achieving this by down-regulating hyperactivated pro-inflammatory proteins and up-regulating hypoactivated anti-inflammatory proteins in the hippocampus. The antidepressant-like effects potentially stemming from the regulation of neurotransmitters and immunomodulation, likely by restoring the balance of M1 and M2 microglia fractions in the hippocampus. Consequently, the CM-AM formula could be explored as a prospective complementary and alternative therapy for depression.